Evolution of the Fe-Rich Phases in Recycled AlSi9Cu3 Cast Alloy during Solution Treatment - Tillova, Eva; Chalupova, Maria; Hurtalova, Lenka (Communications - Scientific letters of the University of Zilina, 2010)
Using recycled aluminium cast alloys is profitable in many aspects. Requiring only 5% of the energy to produce secondary metal as compared to primary metal and generates only 4% of the CO2 emissions, the recycling of aluminium is therefore beneficial of both environmental and economical point of view. AlSi9Cu3 is a very frequently employed die-casting alloy. It is used in almost all fields of pressure die casting, especially in the fabrication various motor mounts, pistons, cylinder heads, heat exchangers, air conditioners or gearings. Al-Si-Cu alloys usually contain Cu and sometimes Mg as the main alloying elements, together with various impurities such as Fe, Mn or Cr. Presence of the Fe impurity enables the crystallization of brittles needles Al5FeSi during solidification, even thought the Fe content is extremely low in a melt, and its presence severely lowers the dynamic fracture toughness of the alloy. Alloying elements such are Mn, Cr, Mo and Be have been used to change the morphology of the Al5 FeSi needles and Al(FeMnMg)Si skeleton (or “Chinese script”) phases. The present study is a part of larger research project, which was conducted to investigate and to provide a better understanding of the solution annealing on the morphology of Fe-rich intermetallic phases in cast Al-Si-Cu alloys. The Fe-rich changes of typical specimens under different solution heat treatment condition were examined using an optical and scanning electron microscope (SEM). The results show that optimal solution treatment causes increasing of mechanical properties, the change of Si-morphology and reduction iron rich phases.